Childhood Abuse and Adult Sociocognitive Skills: Distinguishing Between Self and Other Following Early Trauma. Issue 23 (December 2021) - Hudson, Anna R.; De Coster, Lize; Spoormans, Hanne; Verbeke, Sylvia; Van der Jeught, Kaat; Brass, Marcel; Mueller, Sven C.
Experience of childhood abuse (CA) impairs complex social functioning in children; however, much less is known about its effects on basic sociocognitive processes and even fewer studies have investigated these in adult survivors. Using two behavioral tasks, this study investigated spontaneous theory of mind (ToM) and imitative behavior in 41 women with CA and 26 unaffected comparison (UC) women. In the spontaneous ToM task, UCs showed a larger ToM index than CAs, indicating more facilitation by knowledge of another's false belief. In the imitation–inhibition task, CAs experienced less interference than UCs when observing another's incongruent movements. After controlling for depression, differences in ToM became marginally significant, yet remained highly significant for inhibiting imitative behavior. The findings suggest CA survivors have altered perspective-taking and are less influenced by others' perspectives, potentially due to changes in self-other distinction. Clinical implications regarding therapeutic practice with survivors of CA are discussed.